Analysis of rheological properties of modified bitumen with hybrid polymers - Sarisin, Esma; Yalcin, Erkut; Oner, Julide (Gazi Univ, Fac Engineering Architecture, 2021)
In the application areas, the selection of suitable binders is of great importance in order to build superstructure coating layers that can provide sufficient performance throughout the service life. Due to traffic and climate conditions, the superstructure coating layers are exposed to excessive stresses. Various additives are used for modification in order to improve the properties of bituminous binders, which are one of the main components of flexible superstructure coating layers. With the modification method, the engineering properties of the bituminous binders and the mechanical properties of the asphalt mixes obtained can be improved. Hybrid modification is a method of using two different types of asphalt additives together to achieve an improved modification. Improving the performance of binders and mixtures, reducing costs and utilizing waste materials are among the main objectives of hybrid modification. In the study, the effects of elastomeric (styrene-butadiene-styrene (SBS), Kraton (R) D1101) and plastomeric (Titan (R) 7686) additives and their combination on the rheological properties of the binders were investigated using bitumen modification. As a result of the experimental study, it has been determined that both elastomeric and plastomeric additives improve the high temperature performance of bituminous binders. The plastomeric additive adversely affected the flexibility of the binders. When using the additives together, it was determined that if 3.5% SBS + 1.0% Plastomeric additive is used, the General Directorate of Highways specification requirements were met and a similar performance level was achieved with 4.5% SBS.
Hibrit polimerlerle modifiye edilmiş bitümlü bağlayıcıların reolojik özelliklerinin incelenmesi
Keywords: Bitumen; elastomer; plastomer; hybrid additive; rheology